Ottv Performance In Indonesia, Malaysia And Singapore With A Case Study of The Financial Information and Technology Center Building of The Ministry of Finance of The Republic of Indonesia In Jakarta - Rakhmat Setiadi; Inavonna (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Thermal comfort is essential for the human body to function effectively (at home, school, or in the workplace). A building's thermal performance is one of the primary factors determining the occupant's thermal comfort level. OTTV is an indicator of the building envelope's thermal performance. OTTV (Overall Thermal Transfer Value) is a measure of how much heat from outside the building enters the room through the building envelope (walls, glass, windows, and roof). This value is used to assess the building's thermal performance and energy efficiency. In Indonesia, Malaysia, and Singapore, OTTV performance is measured using formulas established by each country. This study aims to compare three methods for assessing heat transfer through the building envelope in the case of the same office building facade: Singapore's Envelope Thermal Transfer Value (ETTV), Malaysia's Overall Thermal Transfer Value (OTTV), and Indonesia's Overall Thermal Transfer Value (OTTV). These three methods historically originate from the same building regulatory framework, namely ASHRAE Standard 90A-1980 and the ASEAN-USAID/Lawrence Berkeley Laboratory energy conservation program, which were then adapted nationally by each country. A quantitative descriptive method with a comparative approach is applied to measure the Overall Thermal Transfer Value (OTTV) Performance, so that the measurements can be converted to applicable regulations. This case study clearly shows that with the same facade geometry and forming materials, different OTTV/ETTV index values are produced in the three countries with the same compliance result of Not Met. However, these results cannot be compared directly. The dominant heat gain component is solar radiation through fenestration. The implication is that practical design optimization needs to prioritize WWR control, glass thermal performance, and external shading design. Improvements in the U-value of the solid wall and the absorptivity of the solid wall are still beneficial, but in this case it is still less of a priority than solar heat control through fenestration.